The Involvement of the Faculty in Book Selection: The Case of Egerton University Library, Kenya - Kiilu, Peris; Kiilu, Vincent Bob (Scientific & Academic Publishing, 2014)
The study set out to find why users were unhappy with the library collection as was revealed by user surveys carried out by the library. The objectives of the study were to: Evaluate the usefulness of the collection; interrogate tools used by the faculty in book selection; find out whether the entire faculty are involved in book selection and make recommendations for future book selection. Borrower statistics were evaluated against books acquired two and a half years earlier. The study revealed that 43% of books selected over this period were unused. Recommendations for higher circulation include careful evaluation of books prior to acquisition. Keywords: Book selection, Collection development, Collection management, Library acquisitions, Collection building